Diamond grinding tooth, preparation method thereof and thinning grinding wheel
The ultrafine diamond-ceramic bonding agent composite powder grinding wheel was prepared by polymer network gel method, which solved the problem of poor dispersion of ultrafine diamond, improved the grinding effect and sintering efficiency, and achieved excellent performance abrasive preparation.
Patent Information
- Application Number
- CN202411819116.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-07
Smart Images

Figure CN119567120A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of grinding tools, and in particular relates to a diamond gear grinding tool and a preparation method thereof, and a thinning grinding wheel. Background Art
[0002] In recent years, information technology industries such as 5G, Internet of Things, artificial intelligence, and virtual reality have continued to grow with the strong support of national policies. As a key chip in information technology, its demand is also increasing rapidly. Simply put, a chip is a device that can realize specific functions by wiring and etching on a semiconductor wafer. It is widely used in various fields such as new energy vehicles, high-speed rail, aerospace, and solar cells. Hard and brittle materials such as optical glass, silicon wafers, ceramic materials, gallium nitride, silicon carbide wafers, and sapphire have excellent comprehensive properties and are widely used in the chip field. These hard and brittle materials have the advantages of high hardness, strong stability, and good wear resistance, making processing a big problem.
[0003] Ultrafine diamond and nano diamond have poor dispersibility. When they are mixed with micron-sized ceramic binder powder, it is difficult to evenly distribute them in the binder due to the large particle size ratio, resulting in poor grinding effect of the abrasive tool. This has become an important factor restricting the development of ceramic binder ultrafine diamond abrasive tools. In addition, ultrafine diamond has extremely high specific surface area and chemical activity, low antioxidant capacity, and higher sensitivity to harmful elements that can corrode diamond, which limits the direct application of some more mature low-temperature ceramic binders.
[0004] Therefore, how to improve the dispersibility of ultrafine diamond and mix it evenly into the ceramic binder, and how to improve the sintering performance of the ceramic binder and complete good sintering at a lower temperature are the key issues that need to be solved in the preparation of ultrafine diamond ceramic binder abrasive tools with excellent performance. Summary of the invention
[0005] The purpose of the present invention is to provide a diamond gear grinding machine and a preparation method thereof, and a thinning grinding wheel in order to solve at least one of the above problems, so as to solve the problem that the dispersion of ultrafine diamond in the ceramic binder in the prior art is poor. This scheme is based on boroaluminosilicate glass-based ceramic binder and prepares an ultrafine diamond-ceramic binder composite powder grinding wheel through a polymer network gel method to achieve uniform dispersion of ultrafine diamond in the ceramic binder, so that the grinding roughness and wear ratio are better than those of existing commercially available products.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention discloses a method for preparing a diamond gear grinder, comprising the following steps:
[0008] S1: preparing an aqueous solution containing ethyl orthosilicate and ethanol, then adjusting the pH and completely hydrolyzing the ethyl orthosilicate under a water bath condition to obtain an organic mixed solution;
[0009] S2: preparing an aqueous solution containing boric acid and a metal inorganic salt; wherein the metal inorganic salt is an inorganic salt of aluminum and an alkali metal RO and / or an alkaline earth metal R 2 O of inorganic salt to obtain an inorganic mixed solution;
[0010] S3: adding the organic mixed solution prepared in step S1 to the inorganic mixed solution prepared in step S2, stirring evenly, and then sequentially adding a cross-linking monomer and a cross-linking agent, stirring evenly, to obtain a mixed solution;
[0011] S4: adding the ultrafine diamond suspension to the mixed solution obtained in step S3 to obtain a mixed solution;
[0012] S5: adding an initiator to the mixed solution obtained in step S4 and performing water bath polymerization, and obtaining a gel after drying;
[0013] S6: crushing the gel obtained in step S5, calcining it, cold pressing it and sintering it to obtain diamond gear grinding.
[0014] Preferably, the mass dosage of the tetraethyl orthosilicate, boric acid and metal inorganic salt meets the requirements of SiO 2 :Al 2 O 3 :B 2 O 3 : R 2 O+RO=60-70:5-10:10-15:10-15.
[0015] Preferably, in step S1, the mass ratio of the tetraethyl orthosilicate, anhydrous ethanol and deionized water is 20-30:30-40:30-40; the pH is adjusted to 2-3 by 1 mol / L dilute nitric acid; and the temperature of the water bath is 20-25°C.
[0016] Preferably, in step S3, the cross-linking monomer is acrylamide (C 3 H 5 NO), the cross-linking agent is N,N'-methylenebisacrylamide (C 7 H 10 N 2 O 2 ); in step S5, the initiator is ammonium persulfate ((NH 4 )2S 2 O 8); the mass ratio of the cross-linking monomer, the cross-linking agent and the initiator is 60-70%: 10-15%: 20-30%;
[0017] Preferably, in step S4, the ultrafine diamond (particle size: 100-250nm) suspension (mass fraction of 0.05wt%) accounts for 60-70% of the total mass of the mixed solution by mass percentage; the ultrafine diamond suspension is prepared by the following steps:
[0018] Diamond is added to an alkaline solution, and after heat preservation, washing, drying and calcination, it is added to deionized water for ultrasonic dispersion; subsequently, aromatic amine compounds and nitrite compounds are added, and a diamond suspension is obtained by wet grinding; finally, ultrasonic dispersion and centrifugation are performed, and the upper clear liquid is collected to obtain a 0.05wt% ultrafine diamond suspension.
[0019] Preferably, in step S5, the temperature of the water bath polymerization is 60-100° C., and the time is 3-5 min; the water bath polymerization is carried out under magnetic stirring at 50-100 r / min.
[0020] Preferably, in step S6, the sintering is: heated from room temperature to 300-350°C at a heating rate of 2-3°C / min and kept warm for 60-100min, then continued to heat to 550-570°C at a heating rate of 2-3°C / min and kept warm for 60-100min, and finally continued to heat to the maximum sintering temperature at a heating rate of 1-1.5°C / min, and the maximum sintering temperature is 620-650°C.
[0021] More preferably, in step S6, the sintering is: heating from room temperature to 300°C at a heating rate of 2°C / min and keeping warm for 60 minutes, then heating to 550°C at a heating rate of 2°C / min and keeping warm for 60 minutes, and finally heating to the maximum sintering temperature at a heating rate of 1°C / min, and the maximum sintering temperature is 640°C.
[0022] The second aspect of the present invention discloses a diamond grinding tooth, which is prepared by any of the preparation methods described above.
[0023] The third aspect of the present invention discloses a thinning grinding wheel, which is obtained by connecting the diamond grinding teeth as described above to a substrate.
[0024] Preferably, the diamond grinding teeth are adhesively connected to the substrate.
[0025] The working principle of the present invention is:
[0026] The time point when the ultrafine diamond suspension is added to the polymer network gel method system is the key to this method. If it is added too early (before the monomer and cross-linking agent are added), the ultrafine diamond may become less dispersed before the gel is formed; if it is added too late (after the initiator is added), it cannot be guaranteed that the ultrafine diamond can be well dispersed in the gel. Therefore, after the monomer and cross-linking agent are added and before the initiator is added, the highly dispersed ultrafine diamond suspension is added, and then the initiator is added to form the gel, which not only ensures the high dispersion of the ultrafine diamond, but also allows it to be effectively dispersed in the gel.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention prepares an ultrafine diamond-ceramic binder composite powder grinding wheel by a polymer network gel method, and by selecting a suitable time to add ultrafine diamond, it can be highly dispersed in the gel, thereby improving the grinding effect of the grinding wheel as a grinding tool. At the same time, the method can also have a lower sintering temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the process of diamond gear grinding preparation method;
[0030] Figure 2 It is a schematic diagram of the programmed temperature rise of the sintering process in the preparation method;
[0031] Figure 3 is the flexural strength of the ceramic binder of Examples 1-4;
[0032] Figure 4 is the apparent porosity of the ceramic binder of Examples 1-4. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are well known in the art.
[0035] A method for preparing a diamond gear grinder is based on a boroaluminosilicate glass-based ceramic binder and is prepared by a polymer network gel method. The diamond gear grinder is specifically a diamond gear grinder of ultrafine diamond-ceramic binder composite powder, which can be combined on a grinding wheel as a grinding tool.
[0036] The preparation method, such as Figure 1 As shown, the following steps are included:
[0037] S1: preparing an aqueous solution containing ethyl orthosilicate and ethanol, then adjusting the pH and completely hydrolyzing the ethyl orthosilicate under a water bath condition to obtain an organic mixed solution;
[0038] S2: preparing an aqueous solution containing boric acid and a metal inorganic salt; wherein the metal inorganic salt is an inorganic salt of aluminum and an alkali metal RO and / or an alkaline earth metal R 2 O of inorganic salt to obtain an inorganic mixed solution;
[0039] S3: adding the organic mixed solution prepared in step S1 to the inorganic mixed solution prepared in step S2, stirring evenly, and then sequentially adding a cross-linking monomer and a cross-linking agent, stirring evenly, to obtain a mixed solution;
[0040] S4: adding the ultrafine diamond suspension to the mixed solution obtained in step S3 to obtain a mixed solution;
[0041] S5: adding an initiator to the mixed solution obtained in step S4 and performing water bath polymerization, and obtaining a gel after drying;
[0042] S6: crushing the gel obtained in step S5, calcining it, cold pressing it and sintering it to obtain diamond gear grinding.
[0043] Specific:
[0044] The formula of boroaluminosilicate glass ceramic binder is shown in Table 1, where R 2 O and RO represent the oxides of alkaline earth metals and alkali metals respectively:
[0045] Table 1 Formula of boroaluminosilicate glass ceramic binder
[0046]
[0047] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with the mass ratios of the three being 30-40%, 30-40% and 20-30% respectively. Then, adjust the pH value of the solution in the beaker to 2-3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 20-25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0048] Take another beaker and add 130-160mL of deionized water, add boric acid and other oxides in the ceramic binder formula (oxides corresponding to metals other than Si and B, i.e. Al 2 O 3 and R 2 The inorganic salts (such as nitrate) corresponding to O and RO) are added into the beaker according to the proportion in Table 1, and stirred magnetically in a water bath at 45-55°C until the raw materials are completely dissolved.
[0049] Under magnetic stirring conditions, slowly pour the tetraethyl orthosilicate solution into the inorganic salt solution and continue stirring until it is completely mixed. Then add a certain mass ratio of monomer acrylamide (AM) and crosslinking agent N,N'-methylenebisacrylamide (MBA) in sequence and continue stirring until the solution is completely clear.
[0050] The process of preparing the ultrafine diamond suspension is as follows. The ultrafine diamond suspension prepared by this process is used in all subsequent examples:
[0051] (1) The diamond is cleaned by adding it to a 30 wt % potassium hydroxide solution at a temperature of 30-55° C. for 3-21 hours, and then dried and calcined at a temperature of 1000-1200° C. for 1-2 hours;
[0052] (2) placing the calcined diamond in deionized water for ultrasonic dispersion, and then adding aminobenzenesulfonic acid and isoamyl nitrite, both at a concentration of 0.001-0.01 mol / L, to obtain a diamond suspension;
[0053] (3) heating the diamond suspension to 50-80° C. for 2-30 hours to obtain a diamond pretreatment solution;
[0054] (4) dripping the diamond pretreatment liquid into a ball mill with a screen, the speed of the ball mill is 3000-4000 r / min, the grinding medium of the ball mill is zirconium dioxide with a diameter of 30-50 μm, the ball milling liquid is aminobenzoic acid and isoamyl nitrite, the concentrations of the two are 0.005-0.010 mol / L respectively, the mesh diameter of the screen is 2 μm, and after ball milling for 6-9 hours, the diamond suspension flowing out of the screen is collected;
[0055] (5) Ultrasonic dispersion of the collected diamond suspension for 1-2 hours, centrifugation to collect the supernatant, and obtain a 0.05 wt% ultrafine diamond suspension, wherein the particle size of the ultrafine diamond is between 100-250 nm.
[0056] The above-mentioned preparation parameters can be changed arbitrarily within the given range, and the final effect remains basically unchanged.
[0057] The time point when the ultrafine diamond suspension is added to the polymer network gel method system is the key to this method. If it is added too early (before the monomer and cross-linking agent are added), the ultrafine diamond may become less dispersible before the gel is formed; if it is added too late (after the initiator is added), it cannot be guaranteed that the ultrafine diamond can be well dispersed in the gel. Therefore, after the monomer and cross-linking agent are added and before the initiator is added, the highly dispersed ultrafine diamond suspension is added (the amount of ultrafine diamond suspension added accounts for 60-70% of the total mass of the mixed liquid), and then the initiator is added under the action of magnetic stirring at 50-100r / min. The gel can be formed in 3-5 minutes, which not only ensures the high dispersion of the ultrafine diamond, but also allows it to be effectively dispersed in the gel.
[0058] After adding the ultrafine diamond suspension, the clarified mixed solution is transferred to a constant temperature water bath, and the initiator ammonium persulfate (APS) is added under magnetic stirring, and the polymerization reaction is carried out at a certain water bath temperature to obtain a transparent wet gel. The wet gel is placed in a blast drying oven and dried at 100°C to obtain a dry gel (gel).
[0059] When the polymerization temperature is 60-100°C and the ratio of monomer, crosslinking agent and initiator is 4-6:1-3:2-4, a gel with good performance can be prepared in a short time.
[0060] The dry gel is crushed and placed in a muffle furnace for calcination (500-600°C) for 1-2 hours to remove hydrocarbons and crystal water and fully decompose nitrates into oxides, ultimately obtaining ultrafine diamond-ceramic binder composite powder.
[0061] Ultrafine diamond-ceramic binder composite powder is cold pressed into grinding teeth of 30×15×4 on a hydraulic press, and sintered in a muffle furnace to obtain diamond grinding teeth.
[0062] The sintering process is roughly divided into three stages. The specific sintering process curve is as follows: Figure 2 As shown:
[0063] 1. Raise the temperature from room temperature to 300°C at a rate of 2°C / min and keep warm for 60 minutes. This stage is mainly to remove the water and temporary binder (dextrin) added during the cold pressing process. The heating rate of this process should not be too fast to avoid cracking of the sample due to rapid evaporation of the temporary binder.
[0064] 2. Continue to heat up to 550℃ at a heating rate of 2℃ / min and keep it at this temperature for 60min. This stage is mainly to further decompose the residual nitrate in the calcination process. The heating rate should not be too fast, otherwise the sample may crack due to the rapid decomposition of nitrate.
[0065] 3. Continue to heat up to the highest sintering temperature at a heating rate of 1°C / min. At this stage, more liquid phase will appear in the ultrafine diamond-multi-component ceramic binder composite powder, and the volume changes greatly. After sintering, cool down to room temperature with the furnace.
[0066] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0067] In order to investigate the optimal sintering temperature of ultrafine diamond-ceramic binder composite powder, the present invention has developed a sintering scheme with maximum sintering temperatures of 620°C, 630°C, 640°C and 650°C based on a large number of preliminary experiments and literature research.
[0068] Example 1
[0069] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0070] Take another beaker and add 150mL of deionized water to mix the boric acid and Al(NO 3 ) 3 、NaNO 3 Add the mixture into a beaker in a mass ratio of 25%:35%:40% and ethyl orthosilicate in a mass ratio of 3:7, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0071] Under magnetic stirring conditions, slowly pour the ethyl orthosilicate solution into the inorganic salt solution and mix, and continue stirring until it is completely mixed. Then, add a certain mass ratio of monomer AM and crosslinker MBA in sequence, and continue stirring until the solution is completely clear.
[0072] Highly dispersed ultrafine diamond suspension is added so that the mass proportion of ultrafine diamond suspension in the mixed liquid is 65%, and then initiator APS is added to polymerize in a constant temperature water bath under magnetic stirring at 50r / min, and a transparent wet gel can be formed in about 5 minutes.
[0073] The polymerization temperature in the above step is 60°C, and the ratio of monomer, crosslinking agent and initiator is 4:1:2;
[0074] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0075] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0076] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0077] The sintering curve is a curve with a maximum temperature of 620℃. Figure 2 shown.
[0078] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0079] Example 2
[0080] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0081] Take another beaker and add 150mL of deionized water. 3 ) 3 、NaNO 3 Add them into a beaker in a mass ratio of 30%:30%:40% and ethyl orthosilicate in a mass ratio of 3:7, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0082] Under magnetic stirring conditions, slowly pour the ethyl orthosilicate solution into the inorganic salt solution and mix, and continue stirring until it is completely mixed. Then, add a certain mass ratio of monomer AM and crosslinker MBA in sequence, and continue stirring until the solution is completely clear.
[0083] Highly dispersed ultrafine diamond suspension is added so that the mass proportion of ultrafine diamond suspension in the mixed liquid is 65%, and then initiator APS is added to carry out polymerization in a constant temperature water bath under magnetic stirring at 60r / min, and a transparent wet gel can be formed in about 5 minutes.
[0084] The polymerization temperature in the above step is 70°C, and the ratio of monomer, crosslinking agent and initiator is 5:1:3;
[0085] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0086] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0087] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0088] The sintering curve is a curve with a maximum temperature of 630℃. Figure 2 shown.
[0089] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0090] Example 3
[0091] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0092] Take another beaker and add 150mL of deionized water to mix the boric acid and Al(NO 3 ) 3 、NaNO 3 Add them into a beaker in a mass ratio of 35%:35%:40% and ethyl orthosilicate in a mass ratio of 3:7, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0093] Under magnetic stirring conditions, the ethyl orthosilicate solution is slowly poured into the inorganic salt solution to mix, so that the mass proportion of the ultrafine diamond suspension in the mixed solution is 65%, and stirring is continued until it is completely mixed. A certain mass ratio of monomer AM and crosslinking agent MBA are added in sequence, and stirring is continued until the solution is completely clear.
[0094] A highly dispersed ultrafine diamond suspension is added, and then the initiator APS is added to carry out polymerization in a constant temperature water bath under the action of magnetic stirring at 70r / min, and a transparent wet gel can be formed in about 5 minutes.
[0095] The polymerization temperature in the above step is 80°C, and the ratio of monomer, crosslinking agent and initiator is 6:1:2;
[0096] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0097] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0098] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0099] The sintering curve is a curve with a maximum temperature of 640℃. Figure 2 shown.
[0100] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0101] Example 4
[0102] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0103] Take another beaker and add 150mL of deionized water to mix the boric acid and Al(NO 3 ) 3 、NaNO 3 Add them into a beaker in a mass ratio of 20%:40%:40% and ethyl orthosilicate in a mass ratio of 3:7, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0104] Under magnetic stirring conditions, slowly pour the ethyl orthosilicate solution into the inorganic salt solution and mix, and continue stirring until it is completely mixed. Then, add a certain mass ratio of monomer AM and crosslinker MBA in sequence, and continue stirring until the solution is completely clear.
[0105] Highly dispersed ultrafine diamond suspension is added so that the mass proportion of ultrafine diamond suspension in the mixed liquid is 65%, and then initiator APS is added to polymerize in a constant temperature water bath under magnetic stirring at 80r / min, and a transparent wet gel can be formed in about 5 minutes.
[0106] The polymerization temperature in the above step is 90°C, and the ratio of monomer, crosslinking agent and initiator is 6:2:3;
[0107] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0108] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0109] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0110] The sintering curve is a curve with a maximum temperature of 650°C. Figure 2 shown.
[0111] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0112] Comparative Example 1
[0113] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0114] Take another beaker and add 150 mL of deionized water, add boric acid and inorganic salts corresponding to other oxides in the formula (oxides corresponding to metals other than Si and B) into the beaker according to the proportion, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0115] Under magnetic stirring conditions, slowly pour the ethyl orthosilicate solution into the inorganic salt solution and mix, and continue stirring until the mixture is completely mixed.
[0116] Add highly dispersed ultrafine diamond suspension, then add monomer AM and crosslinker MBA in a certain mass ratio, and continue stirring until the solution is completely clear. Then add initiator APS in a constant temperature water bath under magnetic stirring at 70r / min for polymerization, and a transparent wet gel will be formed in about 5 minutes.
[0117] The polymerization temperature in the above step is 80°C, and the ratio of monomer, crosslinking agent and initiator is 6:1:2;
[0118] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0119] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0120] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0121] The sintering curve is a curve with a maximum temperature of 640℃. Figure 2 shown.
[0122] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0123] Comparative Example 2
[0124] Pour deionized water, anhydrous ethanol and tetraethyl orthosilicate into a beaker in sequence, with mass ratios of 40%, 30% and 30% respectively. Then, adjust the pH value of the solution in the beaker to 3 using 1 mol / L dilute nitric acid, and perform magnetic stirring in a 25°C water bath to completely hydrolyze the tetraethyl orthosilicate.
[0125] Take another beaker and add 150 mL of deionized water, add boric acid and inorganic salts corresponding to other oxides in the formula (oxides corresponding to metals other than Si and B) into the beaker according to the proportion, and stir magnetically in a 50°C water bath until the raw materials are completely dissolved.
[0126] Under magnetic stirring conditions, slowly pour the ethyl orthosilicate solution into the inorganic salt solution and mix, and continue stirring until the mixture is completely mixed.
[0127] Add monomer AM and crosslinker MBA in a certain mass ratio in sequence, and continue stirring until the solution is completely clear. Then add initiator APS in a constant temperature water bath under magnetic stirring at 70r / min to polymerize, during which highly dispersed ultrafine diamond suspension is added, and a transparent wet gel is formed in about 5 minutes.
[0128] The polymerization temperature in the above step is 80°C, and the ratio of monomer, crosslinking agent and initiator is 6:1:2;
[0129] The wet gel was placed in a forced air drying oven and dried at 100°C to obtain a dry gel.
[0130] The dry gel is crushed and placed in a muffle furnace for calcination to remove hydrocarbons and crystal water therein and to fully decompose the nitrate into oxides, thereby finally obtaining an ultrafine diamond-ceramic binder composite powder.
[0131] Ultrafine diamond-ceramic binder composite powder is cold pressed into a grinding tooth of 30×15×4 mm in size on a hydraulic press, and sintered in a muffle furnace to obtain a diamond grinding tooth.
[0132] The sintering curve is a curve with a maximum temperature of 640℃. Figure 2 shown.
[0133] The sintered grinding wheel teeth are trimmed according to the predetermined size using a dressing machine. Finally, the teeth are bonded to the base processed by the lathe and grinder using glue. After passing the inspection, they are packaged and stored to obtain the finished grinding wheel.
[0134] Flexural strength and apparent porosity performance testing:
[0135] In order to explore the changing trends of the flexural strength and apparent porosity of the ceramic binder, the multi-component ceramic binder prepared by the polymer network gel method (according to the process of Examples 1-4, but without adding the ultrafine diamond suspension, the other steps are the same) was cold-pressed into sample strips of 55×5×5mm on a hydraulic press and sintered in a muffle furnace.
[0136] Figure 3 , 4 The curves of flexural strength and apparent porosity of multi-component ceramic binder at different sintering temperatures. Figure 3 is the flexural strength, Figure 4 is the apparent porosity. It can be seen that the flexural strength of the ceramic binder first increases and then decreases with the increase of sintering temperature, reaching a maximum value of 75MPa when the sintering temperature is 640℃, which is about 20% higher than that when the sintering temperature is 620℃. The change trend of apparent porosity is opposite to that of flexural strength. It first decreases and then increases with the increase of sintering temperature, and the change range is not large. When the sintering temperature is 640℃, the apparent porosity of the ceramic binder is 27.5%, which is about 5.2% lower than that when the sintering temperature is 620℃. The change law of flexural strength and apparent porosity with sintering temperature well reflects the evolution of the microstructure of ceramic binder at different sintering temperatures.
[0137] When the sintering temperature is too low, there is less liquid phase and more pores in the ceramic binder, and the components are not tightly bonded, so the flexural strength is low and the apparent porosity is high. As the sintering temperature increases, the liquid phase in the binder gradually increases, the pores decrease, and the bonding strength between the components gradually increases, thereby increasing the flexural strength and decreasing the apparent porosity. However, when the sintering temperature is too high, foaming occurs in the binder, the volume expands, and the structure becomes loose, so the flexural strength decreases and the apparent porosity rises slightly.
[0138] Therefore, considering the changes in flexural strength and apparent porosity, the optimal sintering temperature of the multi-component ceramic binder prepared by the polymer network gel method in the present invention should be 640°C.
[0139] Comparative Example 3
[0140] The commercially available Korean EHWA5000J ultrafine diamond-ceramic bond thinning grinding wheel was used.
[0141] Test Case
[0142] 1. Test project: Indium phosphide wafer thinning test: Grind 8-inch Indium phosphide wafers on a DISCO850 thinning machine, with a single-side grinding amount of 100μm, a fine grinding amount of 20μm, a grinding wheel speed of 4800rpm, and grind 100 wafers without trimming.
[0143] 2. Test method: The grinding wheels in Examples 1-4 and Comparative Examples 1-3 were respectively used as indium phosphide wafer thinning grinding wheels to thin 10 indium phosphide wafers respectively, and indium phosphide wafer thinning tests were performed (the results were averaged). Finally, the physical characteristics and wear ratios of the thinned grinding wheels were statistically analyzed. The results are shown in Table 2.
[0144] Table 2 Experimental results of Examples 1-4 and Comparative Examples 1-3
[0145] sample Surface TTV value (μm) Roughness range Ra(nm) Wear ratio (μm / piece) Comparative Example 3 <2 40-50 0.68 Example 1 <2 16-20 0.24 Example 2 <2 17-19 0.30 Example 3 <2 13-16 0.15 Example 4 <2 16-20 0.42 Comparative Example 1 <2 14-20 1.2 Comparative Example 2 >2 30-60 0.23
[0146] It can be seen from the test data that the surface roughness and wear ratio of the thinned grinding wheel (Examples 1-4) prepared by the present invention are better than those of the Korean EHWA grinding wheel (Comparative Example 3).
[0147] If the ultrafine diamond suspension is added too early (before the monomer and the network agent are added), such as in comparative example 1, the wear ratio increases significantly; if the ultrafine diamond suspension is added too late (after the initiator is added), such as in comparative example 2, the surface roughness increases significantly. In addition, the thinning grinding wheel prepared in Example 3 of the present invention (the maximum sintering temperature is 640°C) not only ensures the surface physical characteristics of the indium phosphide wafer after grinding, but also significantly reduces the wear ratio, thereby increasing the service life of the grinding wheel prepared by combining the diamond grinding teeth of the present invention with the substrate as an indium phosphide wafer thinning grinding wheel.
[0148] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing diamond gear grinding, characterized in that: The steps include: S1: preparing an aqueous solution containing ethyl orthosilicate and ethanol, then adjusting the pH and completely hydrolyzing the ethyl orthosilicate under a water bath condition to obtain an organic mixed solution; S2: preparing an aqueous solution containing boric acid and a metal inorganic salt, wherein the metal inorganic salt is an inorganic salt of aluminum and an inorganic salt of an alkali metal RO and / or an alkaline earth metal R2O, to obtain an inorganic mixed solution; S3: adding the organic mixed solution prepared in step S1 to the inorganic mixed solution prepared in step S2, stirring evenly, and then sequentially adding a cross-linking monomer and a cross-linking agent, stirring evenly, to obtain a mixed solution; S4: adding the ultrafine diamond suspension to the mixed solution obtained in step S3 to obtain a mixed solution; S5: adding an initiator to the mixed solution obtained in step S4 and performing water bath polymerization, and obtaining a gel after drying; S6: crushing the gel obtained in step S5, calcining it, cold pressing it and sintering it to obtain diamond gear grinding.
2. The method for preparing diamond gear grinding according to claim 1, characterized in that: The mass dosage of the tetraethyl orthosilicate, boric acid and metal inorganic salt meets the requirement of SiO2:Al2O3:B2O3:R2O+RO=60-70:5-10:10-15:10-15 in diamond gear grinding.
3. The method for preparing diamond gear grinding according to claim 1, characterized in that: In step S1, the mass ratio of the tetraethyl orthosilicate, anhydrous ethanol and deionized water is 20-30:30-40:30-40; the pH is adjusted to 2-3 by 1 mol / L dilute nitric acid; and the temperature of the water bath is 20-25°C.
4. The method for preparing diamond gear grinding according to claim 1, characterized in that: In step S3, the cross-linking monomer is acrylamide, and the cross-linking agent is N,N'-methylenebisacrylamide; in step S5, the initiator is ammonium persulfate; the mass ratio of the cross-linking monomer, the cross-linking agent and the initiator is 60-70%: 10-15%: 20-30%.
5. The method for preparing diamond gear grinding according to claim 1, characterized in that: In step S4, the ultrafine diamond suspension is prepared by the following steps: Diamond is added into an alkaline solution, and after heat preservation, washing, drying and calcination, it is added into deionized water for ultrasonic dispersion; Subsequently, aromatic amine compounds and nitrite compounds are added, and diamond suspension is obtained by wet grinding; finally, ultrasonic dispersion and centrifugation are performed, and the supernatant is collected to obtain an ultrafine diamond suspension.
6. The method for preparing diamond gear grinding according to claim 1, characterized in that: In step S5, the temperature of the water bath polymerization is 60-100° C., and the time is 3-5 min; the water bath polymerization is carried out under magnetic stirring at 50-100 r / min.
7. The method for preparing diamond gear grinding according to claim 1, characterized in that: In step S6, the sintering is: heating from room temperature to 300-350°C at a heating rate of 2-3°C / min and keeping warm for 60-100min, then heating to 550-570°C at a heating rate of 2-3°C / min and keeping warm for 60-100min, and finally heating to the maximum sintering temperature at a heating rate of 1-1.5°C / min, and the maximum sintering temperature is 620-650°C.
8. A diamond gear grinding machine, characterized in that: The method is prepared by any one of claims 1 to 7.
9. A thinning grinding wheel, characterized in that: The diamond grinding wheel as claimed in claim 8 is connected to a substrate to obtain the thinned grinding wheel.
10. A thinning grinding wheel according to claim 9, characterized in that: The diamond grinding teeth are bonded to the matrix.
Citation Information
Patent Citations
Ultrafine diamond and ceramic binding agent stacked abrasive materials and preparation method thereof
CN103273434A
Preparation method of nanometer ceramic bonder type superhard material grinding wheel
CN104802104A
Ultra-high porosity ceramic bond diamond ultra-fine grinding tool and preparation method thereof
CN111331527A
High-porosity ceramic bond diamond grinding wheel and preparation method thereof
CN115519484A
Nanometer ceramic bonding agent and preparation method thereof, silicon-based semiconductor chip back face thinning grinding wheel and preparation method and application of silicon-based semiconductor chip back face thinning grinding wheel
CN118744404A
